Worthless Witnesses? Marginal Voices and Women's Legal Agency in Early Modern England. (October 2019) - Shepard, Alexandra
Abstract: This article explores the distribution of women witnesses in a selection of English church courts between the mid-sixteenth and early eighteenth centuries, in order to assess the extent to which women's participation as witnesses in these jurisdictions might be characterized as a form of legal agency. It shows that women's participation was highly contingent on their marital status and between places and over time and was shaped by the matters in dispute as well as the gender of the litigants for whom they testified. Although poverty did not exclude women witnesses (higher proportions of female witnesses than male claimed to be poor or of limited means), women were more vulnerable than were men to discrediting strategies that cast doubt on their authority in court. Such findings show that the incorporative dimensions of state formation did not deliver new forms of agency to women but depended heavily upon patriarchal norms and constraints.